A Series of Iron Nitrosyl Complexes Fe-NO6-9 and a Fleeting FeNO10 Intermediate en route to a Metalacyclic Iron Nitrosoalkane - Keilwerth, Martin; Hohenberger, Johannes; Heinemann, Frank Wilhelm; Sutter, Jörg; Scheurer, Andreas; Fang, Huayi; Bill, Eckhard; Neese, Frank; Ye, Shengfa; Meyer, Karsten (Journal of the American Chemical Society, 2019)
Iron-Nitrosyls have fascinated chemists for a long time due to the non-innocent nature of the NO ligand that can exist in up to five different oxidation and spin states. Coordination to an open-shell iron center leads to complex electronic structures, which is the reason Enemark and Feltham introduced the Fe-NOn notation.1 In this work, we succeeded to characterize a series of Fe-NO6-9 complexes, including a reactive Fe-NO10 intermediate. All complexes were synthesized with the tris-N-heterocyclic carbene ligand tris[2-(3-mesityl-imidazol-2-ylidene)ethyl]amine (TIMENMes), which is known to support iron in high and low oxidation states. Reaction of NOBF4 with [(TIMENMes)Fe]2+ resulted in formation of the Fe-NO6 compound [(TIMENMes)Fe(NO)(CH3CN)](BF4)3, (1). Stepwise chemical reduction with Zn, Mg, and Na/Hg leads to the isostructural series of high-spin iron nitrosyl complexes Fe-NO7,8,9 (2 - 4). Reduction of Fe-NO9 with Cs electride finally yields the highly reduced Fe-NO10 intermediate, key to formation of [Cs[2.2.2.]crypt][(TIMENMes)Fe(NO)], (5) featuring a metalacyclic Fe-NHC(NO)3− nitrosoalkane unit. All complexes were characterized by single-crystal XRD analyses, temperature and field-dependent SQUID magnetization methods as well as 57Fe Mössbauer, IR, UV/vis, multi-nuclear NMR, and dual-mode EPR spectroscopy. Spectroscopy-based DFT analyses provide insight into the electronic structures of all compounds and allowed assignments of oxidation states to iron and NO ligands. An alternative synthesis to the Fe-NO8 complex was found via oxygenation of the nitride complex [(TIMENMes)Fe(N)](BF4). Surprisingly, the resulting Fe-NO8 species is electronically and structural similar to the [(TIMENMes)Fe(N)]+ precursor. Based on the structural and electronic similarities between this nitrosyl/nitride complex couple, we adopted the strategy, developed by Wieghardt et al.,1 of extending the Enemark & Feltham nomenclature to nitrido complexes, rendering [(TIMENMes)Fe(N)]+ as a Fe-N8 species.
CRIS-Team Scopus Importer:2019-10-22